Prevalence of myopia in school children in Southern Rajasthan - Deshmukh, Utkarsh; Mehta, Rishi (International Journal of Research in Medical Sciences, 2021)
Background: Among the refractive errors, myopia is the most common in school children. Due to myopia, school children are unable to see the blackboard which severely affects their performance. Moreover, they are unable to play outdoor sports thereby hampering their all-round development. Methods: This is a cross-sectional observational and analytical study. All children from 5-12 years attending eye OPD were included. Detailed history was taken and complete ophthalmic examination was done. Low myopia was defined as refractive error of -0.25D to -3D. Moderate myopia was defined refractive error of -3.25 D to -6 D. High myopia was defined as refractive error of ≥-6D. The children were divided into 3 groups according to their age (in years): group-1 (5-7), group-2 (8-9) and group-3 (10-12). The data obtained was subjected to statistical analysis using IBM SPSS version 24. P value was calculated by chi-square test. P<0.05 was considered statistically significant. Results: 153 children were examined, out of which 72 (47.1%) were males and 81 (52.9%) were females. Group-1, group-2 and group-3 had 38, 38, 77 children respectively. Out of 153 children, 26 (16.99%) were found to be myopic. Out of 26 myopic children, males were 11 (42.3%) and females were 15 (57.69%) (p>0.05), Low, moderate and high myopia was found in 19 (73.07%), 6 (23.07%) and 1 (3.84%) child respectively. Conclusions: The prevalence of myopia in school children is 16.99%. There is a need for regular screening of school children to diagnose myopia in them. The limitation of this study is hospital based and small sample size. So, we recommend a community-based study with a larger sample size.